2016
DOI: 10.1039/c6cp03222b
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of gold subnano-structures on a magnetite(111) surface and their interaction with CO

Abstract: Gold deposited on iron oxide surfaces can catalyze the oxidation of carbon monoxide. The adsorption of gold subnano-structures on the Fe-rich termination of the magnetite(111) surface has been investigated using density functional theory. The structural, energetic, and electronic properties of gold/magnetite systems have been examined for vertical and flattened configurations of adsorbed Aun (n = 1-4) species. Single gold adatoms strongly bonded to the iron atoms of the Fe3O4(111) surface appear to be negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 75 publications
(192 reference statements)
0
24
0
Order By: Relevance
“…In particular, the enzyme is anchored thanks to the interaction with citric acid, while the presence of residual oleic acid, which exposes its a-polar tail, not only favours interfacial activation, but also probably protects the enzyme from moisture. Moreover, the heterojunction between magnetite and gold, which have different work functions [27,28], inducing a Fe 3 O 4 surface polarity modification determines an enhanced affinity with citric acid, favouring an increased stability, e.g. strong ionic interaction [29].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the enzyme is anchored thanks to the interaction with citric acid, while the presence of residual oleic acid, which exposes its a-polar tail, not only favours interfacial activation, but also probably protects the enzyme from moisture. Moreover, the heterojunction between magnetite and gold, which have different work functions [27,28], inducing a Fe 3 O 4 surface polarity modification determines an enhanced affinity with citric acid, favouring an increased stability, e.g. strong ionic interaction [29].…”
Section: Resultsmentioning
confidence: 99%
“…CH 2 OHCHOHCO(ads) on the surface of Au(111) can be converted very easily into C1/C2 products, [91] which is possibly due to the lowest d‐band center among the three noble metals (−3.56 eV) [32] destabilizing RCO(ads). Besides, it has been widely reported that CO(ads) can further lower the d‐band center of Au (e. g. 3 eV for Au monomer [145] ), as the 5d bands narrows and the number of states reduces near EF (Fermi level), which implies a promoting effect of CO(ads) on the catalytic activity of Au. A lower d‐band center would increase the filling of the anti‐bonding orbital of the adsorbed molecule and therefore facilitates the dissociation.…”
Section: Parallel Pathways Proposed As the Major Reaction Mechanism Omentioning
confidence: 99%
“…While the interaction with organophosphonates was studied with several other iron oxides, there are almost no investigations on magnetite/maghemite nanoparticles. Magnetite particles seem to consist predominately of (111) surfaces, which means that the top layer consists mainly of iron ions. ,, Daou et al investigated the surface complex starting from hydroxylated magnetite at pH = 3 and found that phosphatation occurs by interaction of Fe 3+ in octahedral sites with the formation of monoprotonated bimolecular species . However, attachment mechanisms can be different, when starting from a carboxylated magnetite/maghemite surface.…”
Section: Resultsmentioning
confidence: 99%